2019
DOI: 10.3390/ma12223723
|View full text |Cite
|
Sign up to set email alerts
|

New Damage Evolution Law for Steel–Asphalt Concrete Composite Pavement Considering Wheel Load and Temperature Variation

Abstract: Epoxy asphalt (EA) concrete is widely used in constructing long-span steel bridge pavements (SBDPs). This study aims to derive a fatigue damage evolution law, conducting an experimental investigation of SBDP. First, a general theoretical form of the fatigue damage evolution law of materials is established based on the thermal motion of atoms. Then, fatigue experiments demonstrate that this evolution law well represents the known damage–life relationships of SBDP. Taking into account the experimental relationsh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Twenty universities and scientific centres contributed with their original research papers to this Special Issue of Materials . The issues covered can be divided into five main topics: Characterization of recycled materials in asphalt concrete mixtures, such as waste of sanitary ceramics [ 23 ], crumb rubber (CR) from waste tires [ 24 , 25 , 26 ] and reclaimed asphalt (RA) [ 27 , 28 ]; Investigation of natural [ 28 ] or bio-based [ 29 ] materials used as rejuvenators in recycled asphalt applications; Study of rheological and fatigue behaviour of bituminous materials with [ 30 ] and without [ 31 ] the use of renewable bio-materials; Evaluation of lubricant characteristics of graphite nanoplatelets [ 32 ]; Fatigue life prediction model for materials employed on long-span steel bridge decks [ 33 ]. …”
Section: Short Description Of the Articles Published In This Special ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty universities and scientific centres contributed with their original research papers to this Special Issue of Materials . The issues covered can be divided into five main topics: Characterization of recycled materials in asphalt concrete mixtures, such as waste of sanitary ceramics [ 23 ], crumb rubber (CR) from waste tires [ 24 , 25 , 26 ] and reclaimed asphalt (RA) [ 27 , 28 ]; Investigation of natural [ 28 ] or bio-based [ 29 ] materials used as rejuvenators in recycled asphalt applications; Study of rheological and fatigue behaviour of bituminous materials with [ 30 ] and without [ 31 ] the use of renewable bio-materials; Evaluation of lubricant characteristics of graphite nanoplatelets [ 32 ]; Fatigue life prediction model for materials employed on long-span steel bridge decks [ 33 ]. …”
Section: Short Description Of the Articles Published In This Special ...mentioning
confidence: 99%
“…In the paper presented by Xu et al [ 33 ], a fatigue life prediction model for asphalt concretes laid on long-span steel bridge decks was established based on the mechanism of fatigue damage evolution of materials from the microscopic perspective. Moreover, the reliability of the model was verified by fatigue tests performed on epoxy asphalt (EA), stone matrix asphalt (SMA) and gussasphalt (GA).…”
Section: Short Description Of the Articles Published In This Special ...mentioning
confidence: 99%
“…According to the structural characteristics of Jiangyin Yangtze River Bridge, the composite beams for the fatigue test were designed based on the models. Under the action of standard axle load (BZZ-100), the cyclic load amplitude was 5 kN [46]. Generally, the traveling speed of vehicles on the steel bridge surface is between 50 km/h and 100 km/h, and the corresponding fatigue loading frequency is 5-10 Hz.…”
Section: Fatigue Measurement Of the Composite Beam For The Steel Deckmentioning
confidence: 99%
“…At present, research on the effect of the wheel position on the fatigue performance of bridge decks mainly focuses on steel decks [33][34][35][36][37]. For example, Zhou et al [34] showed that the lateral position of a vehicle was very sensitive to the transverse stress of the steel bridge deck and the fatigue damage of key parts.…”
Section: Introductionmentioning
confidence: 99%